Variations on the nutritional status of eucalypt as influenced by the genetic material and age of tree - Wadt, Paulo Guilherme Salvador; Novais, Roberto Ferreira de; Alvarez, Victor Hugo; Barros, Nairam Félix de; Dias, Luiz Eduardo (Pesquisa Agropecuaria Brasileira, 1999)
The Diagnosis and Recommendation System (DRIS) was applied to eucalypt trees (hybrids of Eucalyptus grandis x E. urophylla) with different ages and growing under different environmental conditions for three different clones. The basic data were obtained from 1,986 trees of commercial stands cultivated in the states of Espírito Santo and south Bahia, Brazil. The DRIS indices were calculated using the Beaufils’ Range formula and grouped according to the Nutrient Application Potential Response method. The objective of this paper was to evaluate the N, P and Ca status in eucalypt trees, regarding the tree ages and genetic materials. The DRIS indices discriminated differences in the nutritional status of the trees, both in relation to age and the genetic materials (clones). The results indicated that the deficiency of N and Ca tended to decrease with tree age, whereas the P deficiency tended to increase. Furthermore, of the three evaluated clones, those numbered 00014 and 00034 showed opposite trends regarding to N, P, and Ca nutrition, and the clone numbered 00021, in general, presented the highest degree of unbalanced nutrition of N, P and Ca.